Preparation method of toughened and antibacterial PLA-based melt-blown non-woven material, product and application of toughened and antibacterial PLA-based melt-blown non-woven material

Through the blending and modification method, MBS and antibacterial agents Nano-ZnO and PHMG were added, and PEG and interface compatibility were introduced, which solved the problems of poor toughness and difficulty in antibacterial modification of PLA-based meltblown nonwovens, and achieved the toughening and efficient antibacterial effect of the material.

CN119507072APending Publication Date: 2025-02-25TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411705713.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing PLA-based meltblown nonwovens have poor toughness and difficulty in antibacterial modification, resulting in brittleness problems and insufficient antibacterial performance in their applications.

Method used

By blending and modification method, methyl methacrylate-butadiene-styrene copolymer (MBS) was added to enhance toughness, and nano zinc oxide (Nano-ZnO) and polyhexamethylene monoguanidine hydrochloride (PHMG) were used as antibacterial agents, combining polyethylene glycol (PEG) and interface compatibility agents to optimize material compatibility and processing properties.

Benefits of technology

The toughening and antibacterial modification of PLA-based meltblown nonwoven materials has been achieved, which has improved the overall performance of the material, including improving the antibacterial performance, toughness and processing performance, and solved the problem of insufficient brittleness and antibacterial performance of the material in application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507072A_ABST
    Figure CN119507072A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method, a product and application of a toughened and antibacterial PLA-based melt-blown non-woven material, and belongs to the technical field of spinning. The toughened and antibacterial PLA-based master batch disclosed by the invention is prepared from the following raw material components in parts by mass: 84 to 90 parts of polylactic resin, 4 parts of methyl methacrylate-butadiene-styrene copolymer, 1 part of nano zinc oxide, 0.5 part of polyhexamethylene guanidine hydrochloride, 4 to 10 parts of polyethylene glycol and 0.5 part of C1A type compatilizer. And melting and spinning the toughened and antibacterial PLA-based master batch, and sequentially carrying out hot pressing treatment and corona electret treatment to obtain the toughened and antibacterial PLA-based melt-blown non-woven material. The PLA-based melt-blown non-woven material provided by the invention has good antibacterial property and mechanical property, and has relatively strong market competitiveness and relatively good industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spinning, and in particular to a preparation method, product and application of a toughened and antibacterial PLA-based melt-blown nonwoven material. Background Art

[0002] Meltblown nonwoven forming technology is an efficient, green and commercialized micron-level fiber preparation technology. The ultrafine fiber nonwoven materials produced by it exhibit excellent filtration performance, breathability and low price. They have been widely used in medical and health care, filtration separation and personal protection.

[0003] Up to now, the main raw material of meltblown nonwoven materials is still polypropylene (PP). However, with the large-scale use of PP-based meltblown nonwoven materials, discarded PP-based meltblown nonwoven materials are thrown into nature, causing white pollution that is difficult to eliminate, aggravating the problem of environmental pollution. Polylactic acid (PLA) is a new type of material with renewable and biodegradable properties. It can not only alleviate the energy crisis but also be degraded by microorganisms without causing any harm to the environment. In addition, due to its good physical properties and biocompatibility, it is considered to be an ideal substitute for traditional petrochemical plastics. Therefore, how to prepare PLA-based antibacterial meltblown nonwoven materials has become a research hotspot in the field of synthetic fibers. At present, there have been studies on PLA-based meltblown nonwoven materials. However, the poor toughness of PLA itself will lead to the brittleness of meltblown nonwoven products, limiting its further development in the field of synthetic fibers. Due to the poor toughness of PLA, its meltblown processing performance will also be greatly affected.

[0004] People's requirements for meltblown nonwoven materials are not limited to their ability to filter particles, but they pay more attention to the antibacterial function of meltblown nonwoven materials. Meltblown nonwoven materials themselves have excellent filtering properties, making it easy for bacteria to adsorb on the surface or even inside the material, and the degradation of PLA can further provide a source of nutrients for bacterial proliferation, increasing the risk of human infection with viruses. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a preparation method, product and application of a toughened and antibacterial PLA-based melt-blown nonwoven material.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is a toughened antibacterial PLA-based masterbatch, wherein the raw materials include the following components by weight: 84-90 parts of polylactic acid resin, 4 parts of methyl methacrylate-butadiene-styrene copolymer, 1 part of nano zinc oxide, 0.5 parts of polyhexamethylene guanidine hydrochloride, 4-10 parts of polyethylene glycol and 0.5 parts of C1A type compatibilizer.

[0008] The second technical solution of the present invention is a method for preparing a toughened antibacterial PLA-based masterbatch, which comprises melt-blending the raw materials in the above technical solution, extruding and granulating to obtain the toughened antibacterial PLA-based masterbatch; the melt-blending temperature is 145°C-180°C.

[0009] The third technical solution of the present invention is a toughened and antibacterial PLA-based melt-blown nonwoven material, the raw material of which is the toughened and antibacterial PLA-based masterbatch mentioned above.

[0010] The fourth technical solution of the present invention is a method for preparing a toughened antibacterial PLA-based melt-blown nonwoven material, which comprises melting and spinning the toughened antibacterial PLA-based masterbatch, and then performing a hot pressing treatment and a corona electret treatment in sequence.

[0011] A fifth technical solution of the present invention is an application of the toughened antibacterial PLA-based masterbatch or the toughened antibacterial PLA-based meltblown nonwoven material in the fields of medical care, filtration separation or personal protection.

[0012] The present invention discloses the following technical effects:

[0013] In the present invention, MBS provides good toughness for the product, and the material transitions from brittle fracture to tough fracture; Nano-ZnO antibacterial agent is successfully loaded onto PHMH through twin-screw reactive extrusion, and the synergistic antibacterial effect produced by Nano-ZnO and PHMG has excellent antibacterial properties. The present invention also improves the compatibility between the components through the interfacial compatibilizer, which not only helps each component to fully play its own role, but also the overall compatibility increases the mechanical properties and processability of the composite material. The introduction of PEG significantly improves the processing performance of the material, and the decomposition of PLA is improved. In addition, the introduction of PEG also improves the crystallization performance and toughness of the material. Finally, a PLA-based melt-blown nonwoven material with excellent comprehensive performance is obtained.

[0014] In view of the problems of poor toughness, great difficulty in antibacterial modification, complex operation, poor antibacterial performance, and difficulty in maintaining antibacterial performance for a long time of PLA melt-blown nonwoven materials, the present invention adopts a method of blending antibacterial modification and a method of compounding and using multiple antibacterial agents, and realizes the toughening modification, antibacterial modification, and optimized processing performance of PLA in one step; directly adding antibacterial agents to the polylactic acid matrix material to participate in the processing and molding of melt-blown materials, which can add rich raw materials, simple process, low processing cost, excellent antibacterial performance, and greatly improved antibacterial time. The present invention takes into account the timeliness of material antibacterial and the cost of material processing and preparation, can meet the requirements of melt-blown materials for antibacterial in most fields, has the advantages of low cost, simple method, and high feasibility in actual production, and has strong market competitiveness and good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 The morphology of the antibacterial agent (Nano-ZnO and PHMG) in Example 1, the cross-sectional view of the toughened antibacterial PLA-based masterbatch, and the morphology of the meltblown fabric fibers in Example 1 and Comparative Example 5;

[0017] Figure 2 is the melting and crystallization curve of the antibacterial agent PHMG;

[0018] Figure 3 The antibacterial performance of the meltblown fabrics of Examples 1-4 and Comparative Example 5 was tested. DETAILED DESCRIPTION

[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0020] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0021] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0024] Blending modification of polylactic acid (PLA) is a low-cost, simple-to-operate, and effective modification method. The present invention targets the poor toughness of PLA and the deficiencies in processability and antibacterial properties by melt blending modification of PLA through compounding of multiple additives. Among them, the toughening of PLA is achieved by adding methyl methacrylate-butadiene-styrene copolymer (MBS). MBS is a terpolymer polymerized from methyl methacrylate, butadiene, and styrene. The copolymer appears as a rubber phase in the PLA matrix material. When external force acts on the material, the silver streaks caused by the rubber phase can effectively absorb the impact energy and prevent the material from brittle fracture. In addition, when MBS is subjected to high-load impact, the rubber phase will undergo stress relaxation and creep, thereby inducing cavitation and causing shear yield of the material, thereby improving the toughness of the material. The antibacterial property of the material is achieved by adding nano zinc oxide (Nano-ZnO) and polyhexamethylene guanidine hydrochloride (PHMG). These two materials will undergo organic-inorganic hybridization in the twin-screw extruder and eventually self-assemble into microspheres with Nano-ZnO as the shell structure and PHMG as the core structure. The appearance of microspheres can greatly improve the dispersibility of Nano-ZnO and Zn 2+ The release amount of the material is increased to achieve efficient antibacterial properties. In addition, polyethylene glycol (PEG) is introduced to improve the comprehensive performance of the material, which is specifically reflected in the fact that PEG can improve the processing performance, toughness, crystallization performance, etc. of PLA melt-blown. In order to increase the interfacial compatibility between the materials, the present invention also introduces a C1A type interfacial compatibility agent, which is a terpolymer containing styrene and maleic anhydride, which can improve the interfacial compatibility between different particles.

[0025] The first aspect of the present invention provides a toughened antibacterial PLA-based masterbatch, wherein the raw materials include the following components by weight: 84-90 parts of polylactic acid resin, 4 parts of methyl methacrylate-butadiene-styrene copolymer, 1 part of nano zinc oxide, 0.5 parts of polyhexamethylene guanidine hydrochloride, 4-10 parts of polyethylene glycol and 0.5 parts of C1A type compatibilizer.

[0026] In some embodiments of the present invention, the polylactic acid resin is spherical solid particles with a particle size of ≤3 mm and a melt index of 2 to 12 g / 10 min; the diameter of the nano zinc oxide is ≤50 nm; the polyhexamethylene guanidine hydrochloride is a solid powder with a diameter of ≤100 μm; the MBS is a white solid powder; the PEG is a white flaky solid; and the C1A type compatibilizer is a colorless transparent particle.

[0027] The second aspect of the present invention provides a method for preparing a toughened antibacterial PLA-based masterbatch, wherein the raw materials in the above technical scheme are melt-blended, extruded, and granulated to obtain the toughened antibacterial PLA-based masterbatch; the melt-blending temperature is 145°C-180°C.

[0028] In some embodiments of the present invention, before the raw materials are melt-blended, a step of drying the raw materials is also included; wherein the polylactic acid resin is dried: the polylactic acid resin is placed in a vacuum drum for drying, the drying temperature is 50° C., the vacuum degree is -0.1 MPa, the drying time is 17 hours, and the moisture content of the polylactic acid resin is ≤0.005%;

[0029] Drying of MBS: Place MBS in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 110°C, a vacuum degree of -0.1MPa, and a drying time of 8h; MBS moisture content ≤ 0.01%;

[0030] Drying Nano-ZnO: Place the Nano-ZnO in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 120°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of Nano-ZnO is ≤0.01%;

[0031] Drying PHMG: Place PHMG in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 120°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of PHMG is ≤0.01%;

[0032] Drying PEG: Place PEG in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 50°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of PEG is ≤0.01%;

[0033] Drying treatment of C1A type compatibilizer: Place C1A type compatibilizer in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 100°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of C1A type compatibilizer is ≤0.01%.

[0034] In the present invention, the above raw materials are all commercially available products and can be purchased.

[0035] In some embodiments of the present invention, the raw materials are melt-blended, extruded, and granulated. The specific steps are as follows: after the dried raw materials are configured in proportion, PLA resin is added from the main feeding port of the twin-screw extruder, and the uniformly mixed additives (MBS, Nano-ZnO, PHMG, PEG, C1A type compatibilizer) are added from the side feeding port. The twin-screw extruder is used for low-temperature heating and melting at 145°C-180°C, shear dispersion, uniform mixing, and homogenization extrusion into a melt stream, which is then cooled into strips with deionized water, and then pelletized by a pelletizer to prepare a toughened antibacterial PLA-based masterbatch.

[0036] The third aspect of the present invention provides a toughened and antibacterial PLA-based melt-blown nonwoven material, the raw material of which is the toughened and antibacterial PLA-based masterbatch.

[0037] The fourth aspect of the present invention provides a method for preparing a toughened antibacterial PLA-based melt-blown nonwoven material, wherein the toughened antibacterial PLA-based masterbatch is melted and spun, and then subjected to hot pressing treatment and corona electret treatment in sequence.

[0038] In some embodiments of the present invention, before melting the toughened antibacterial PLA-based masterbatch, the step of drying the toughened antibacterial PLA-based masterbatch in a vacuum environment at 40-60° C. to a moisture content of ≤50 ppm is also included.

[0039] In some embodiments of the present invention, the specific steps of melting and spinning the toughened antibacterial PLA masterbatch are: setting the temperature of the melt-blowing screw heating zone to 135°C-180°C, the nozzle temperature to 200°C-210°C, the hot air temperature to 200°C-210°C, the die pressure to 3-5MPa, and the receiving distance to 30-40cm. After the above conditions reach the set value, keep for 2 hours; add the dried toughened antibacterial PLA masterbatch to the melt-blowing machine, and the toughened antibacterial PLA masterbatch forms a melt state under the conditions of 135°C-180°C and 3-5MPa. After the shear extrusion of the screw zone, the melt stream is extruded through the metering pump and then through the die spinneret at high pressure. The melt stream is further elongated and thinned under the action of hot air, and finally cooled by cold air to form a semi-melt state and received by the winding device.

[0040] In some embodiments of the present invention, the temperature of the hot pressing treatment is 135°C, the pressure is 0.1 MPa, and the time is 7s; the parameters of the corona electret treatment are set as: the electret voltage is 30kV, the electret time is 2min, and the electret distance is 35cm.

[0041] The fifth aspect of the present invention provides an application of the toughened antibacterial PLA-based masterbatch or the toughened antibacterial PLA-based meltblown nonwoven material in the fields of medical care, filtration separation or personal protection.

[0042] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0043] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0044] Example 1

[0045] (1) Drying of raw materials:

[0046] Drying the polylactic acid resin: placing the polylactic acid resin in a vacuum drum for drying, the drying temperature is 50°C, the vacuum degree is -0.1MPa, the drying time is 17h, and the moisture content of the polylactic acid resin is ≤0.005%;

[0047] Drying of MBS: Place MBS in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 110°C, a vacuum degree of -0.1MPa, and a drying time of 8h; MBS moisture content ≤ 0.01%;

[0048] Drying Nano-ZnO: Place the Nano-ZnO in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 120°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of Nano-ZnO is ≤0.01%;

[0049] Drying PHMG: Place PHMG in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 120°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of PHMG is ≤0.01%;

[0050] Drying PEG: Place PEG in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 50°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of PEG is ≤0.01%;

[0051] Drying treatment of C1A type compatibilizer: Place C1A type compatibilizer in a quartz container and then dry it in a vacuum drying oven at a drying temperature of 100°C, a vacuum degree of -0.1MPa, and a drying time of 8h; the moisture content of C1A type compatibilizer is ≤0.01%;

[0052] (2) Preparation of toughened antibacterial PLA-based masterbatch: The dried raw materials were mixed in proportion (84 parts of PLA, 4 parts of MBS, 1 part of Nano-ZnO, 0.5 parts of PHMG, 10 parts of PEG and 0.5 parts of C1A-type compatibilizer), PLA resin was added from the main feed port of a twin-screw extruder, and the evenly mixed additives (MBS, Nano-ZnO, PHMG, PEG, C1A-type compatibilizer) were added from the side feed port. The twin-screw extruder was used for low-temperature heating and melting at 180°C, shear dispersion, uniform mixing, and homogenization extrusion into a molten stream, which was then cooled into strips with deionized water and pelletized by a pelletizer to prepare a toughened antibacterial PLA-based masterbatch.

[0053] (3) Drying the toughened antibacterial PLA-based masterbatch: Dry the prepared toughened antibacterial PLA-based masterbatch in a vacuum environment at 60° C. until the moisture content is ≤50 ppm.

[0054] (4) Preparation of toughened antibacterial PLA-based melt-blown nonwoven materials: Set the melt-blowing screw heating zone temperature to 135°C-180°C, the nozzle temperature to 200°C, the hot air temperature to 200°C, the die pressure to 4MPa, and the receiving distance to 35cm. After the above conditions reach the set value, maintain for 2 hours; add the dried toughened antibacterial PLA-based masterbatch into the melt-blown machine, and the toughened antibacterial PLA-based masterbatch forms a melt state under the conditions of 135°C-180°C and 4MPa. After the shear extrusion action of the screw zone, it is extruded through the metering pump and then through the die spinneret at high pressure to form a melt stream. The melt stream is further elongated and thinned under the action of hot air, and finally cooled by cold air to form a semi-melt state and received by the winding device.

[0055] (5) Hot pressing treatment: The PLA-based antibacterial meltblown fabric was hot pressed by a mechanical pressurizing device at a temperature of 135°C, a pressure of 0.1 MPa, and a time of 7 seconds.

[0056] (6) Corona electret treatment: The toughened antibacterial PLA-based meltblown nonwoven material was subjected to corona electret treatment to obtain the final toughened antibacterial PLA-based antibacterial meltblown fabric (referred to as meltblown fabric). The parameters of the corona electret treatment were: electret voltage of 30 kV, electret time of 2 min, and electret distance of 35 cm.

[0057] Example 2

[0058] The same as Example 1, except that the raw materials are: 90 parts of PLA, 4 parts of MBS, 1 part of Nano-ZnO, 0.5 parts of PHMG, 0.5 parts of C1A type compatibilizer and 4 parts of PEG; other steps and parameters are the same as Example 1.

[0059] Example 3

[0060] The same as Example 1, except that the raw materials are: 88 parts of PLA, 4 parts of MBS, 1 part of Nano-ZnO, 0.5 parts of PHMG, 0.5 parts of C1A type compatibilizer and 6 parts of PEG; other steps and parameters are the same as Example 1.

[0061] Example 4

[0062] The same as Example 1, except that the raw materials are: 86 parts of PLA, 4 parts of MBS, 1 part of Nano-ZnO, 0.5 parts of PHMG, 0.5 parts of C1A type compatibilizer and 8 parts of PEG; other steps and parameters are the same as Example 1.

[0063] Comparative Example 1

[0064] The same as Example 1, except that the raw material is only PLA, and MBS, Nano-ZnO, PHMG, C1A type compatibilizer and PEG are not added; the other steps and parameters are the same as Example 1.

[0065] Comparative Example 2

[0066] The same as Example 1, except that the raw materials are: 95.5 parts of PLA, 4 parts of MBS, and 0.5 parts of C1A type compatibilizer; the other steps and parameters are the same as Example 1.

[0067] Comparative Example 3

[0068] The same as Example 1, except that the raw materials are: 94.5 parts of PLA, 4 parts of MBS, 0.5 parts of C1A type compatibilizer, and 1 part of Nano-ZnO; other steps and parameters are the same as Example 1.

[0069] Comparative Example 4

[0070] The same as Example 1, except that the raw materials are: 94.5 parts of PLA, 4 parts of MBS, 0.5 parts of C1A type compatibilizer, and 1 part of PHMG; the other steps and parameters are the same as Example 1.

[0071] Comparative Example 5

[0072] The same as Example 1, except that the raw materials are: 94 parts of PLA, 4 parts of MBS, 1 part of Nano-ZnO, 0.5 parts of PHMG and 0.5 parts of C1A type compatibilizer; other steps and parameters are the same as Example 1.

[0073] Performance Testing

[0074] The product structure and performance tests prepared in Examples 1-4 and Comparative Examples 1-5 specifically include basic structure and performance tests (average fiber diameter, breaking strength, air permeability, filtration efficiency, ventilation resistance), antibacterial performance tests (agar plate diffusion method antibacterial performance test, oscillation method antibacterial performance test). The relevant tests are as follows.

[0075] Test Example 1: Test of basic structure and performance;

[0076] The Czech TESCAN MIRALMS scanning electron microscope produced by Tesken was used to observe the morphology and dispersion of the antimicrobial agent, the cross-sectional morphology of the PLA-based masterbatch and the distribution of the antimicrobial agent, the fiber morphology in the meltblown fabric and the morphology of the antimicrobial agent. The fiber diameter was tested using the ipwin diameter analysis software.

[0077] Depend on Figure 1 It can be seen that Nano-ZnO presents a cluster morphology of 20-50nm. PHMG presents an irregular shape. Many spherical particles formed by Nano-ZnO and PHMG appear in the cross section of the masterbatch of Test Example 1 (i.e., Example 1). This is because PHMG will form a molten state during the preparation of the masterbatch, and due to the poor compatibility of PHMG with PP, it will form a shape similar to an island structure, and Nano-ZnO will interact with PHMG and adhere to the surface of PHMG. In addition, compared with Comparative Example 5, the fiber diameter of the meltblown cloth in Example 1 is significantly thinner, and the number of nano-scale fibers has increased significantly.

[0078] The antimicrobial agent PHMG was tested using a DSC6000 differential scanning calorimeter produced by PerkinElmer Instruments, Inc., and the melting and crystallization curves were drawn.

[0079] Depend on Figure 2 It can be seen that PHMG has a melting peak at around 90°C, while the temperature can reach 180°C during the preparation of the masterbatch, indicating that PHMG forms a molten state during the processing, which further proves that Figure 1 The spherical particles in the cross section of the medium masterbatch are PHMG.

[0080] Referring to the national standard GB_T 24218.3-2010 "Nonwoven fabric test methods Part 3: Determination of breaking strength and breaking elongation (strip method)", the HZ-10075 desktop computer servo material testing machine produced by Lixian Instrument Technology Co., Ltd. was used to test the front breaking strength of the fabric (test results are shown in Table 1). The sample size is a 5cm*12cm strip, the effective clamping distance is 10cm, and the tensile speed is 10mm / min.

[0081] According to the national standard GB / T 2418.15-2018 "Nonwoven Test Methods Part 15: Determination of Air Permeability", the test was carried out using the YG461E fully automatic air permeability meter produced by Ningbo Textile Instruments (test results are shown in Table 1). The sample size is 8cm*8cm square fabric sample, and the effective test area is 20cm 2 .

[0082] According to the national standard GB / T 38413-2019 "Test Method for Filtration Performance of Fine Particles in Textiles", the GB-KF30010 particle filtration efficiency tester produced by Guangzhou Marking Packaging Equipment Co., Ltd. was used to test the filtration performance and ventilation resistance (test results are shown in Table 1). The sample size is 13cm*13cm, and the effective test area is 100cm 2 .

[0083] Table 1

[0084]

[0085]

[0086] It can be seen from Examples 1-4 and Comparative Example 5 in Table 1 that the PLA-based antibacterial meltblown cloth exhibits excellent filtration performance after adding PEG. With the increase of PEG content, the filtration efficiency shows an upward trend and the pressure drop is further reduced. This is because a large number of nanofibers are produced under the interaction between PLA and PEG, which leads to an improvement in filtration efficiency.

[0087] Test Example 2: Antibacterial performance test using agar plate diffusion method

[0088] The antibacterial performance of the meltblown material of the present invention was tested with reference to GB / T 20944.1-2007 "Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method". The evaluation criteria are shown in Table 2. The test results are shown in Table 2. Figure 3 shown.

[0089] Table 2

[0090]

[0091]

[0092] Figure 3 It is shown that there is no antibacterial band in Comparative Example 5 (sample without PEG), which indicates that the melt-blown cloth processed by Nano-ZnO, PHMG and PLA through blending does not have the property of dissolving antibacterial, which is related to the way of antibacterial agent and PLA base. In the process of blending, the antibacterial agent will only appear inside the PLA fiber or be embedded in the surface. In contrast, the remaining 4 embodiments (i.e., Examples 1, 2, 3, 4, samples containing PEG) all have obvious antibacterial bands, and the diameter of the antibacterial band increases significantly with the increase of PEG content, indicating that the addition of PEG gives the PLA-based melt-blown cloth the ability of dissolution-type antibacterial, and further releases the antibacterial ability of Nano-ZnO and PHMG. The reason for this phenomenon is due to the excellent water solubility of PEG. In the antibacterial process, the PEG on the surface of the PLA fiber is affected by moisture and will carry the internal antibacterial agent into the culture medium, which leads to the appearance of the antibacterial band, giving the PLA-based melt-blown cloth the ability of dissolving antibacterial.

[0093] Test Example 3: Oscillation method antibacterial performance test

[0094] The antibacterial property of the PLA-based meltblown material of the present invention was tested according to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", and the test results are shown in Table 3 below.

[0095] Table 3

[0096]

[0097]

[0098] As shown in Table 3, the PLA meltblown cloth without adding antibacterial ingredients (Nano-ZnO, PHMG) has an antibacterial rate of 0 against Staphylococcus aureus and Escherichia coli, indicating that it does not have antibacterial ability itself; the PLA-based meltblown cloth with Nano-ZnO added (Comparative Example 3) exhibits certain antibacterial ability, but the antibacterial ability is limited, and the antibacterial rate is below 40% when the Nano-ZnO content is 1 part; the antibacterial rate of the PLA-based meltblown cloth when the PHMG addition amount is 1 part is below 20% (Comparative Example 4); the PLA-based meltblown cloth with both Nano-ZnO and PHMG added exhibits excellent antibacterial ability (Examples 1-4), which is due to its antibacterial synergistic effect, and on this basis, the addition of PEG has a certain antibacterial enhancement effect, which is caused by the dissolution of PEG.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A toughened antibacterial PLA-based masterbatch, characterized in that: The raw materials include the following components by weight: 84-90 parts of polylactic acid resin, 4 parts of methyl methacrylate-butadiene-styrene copolymer, 1 part of nano zinc oxide, 0.5 parts of polyhexamethylene guanidine hydrochloride, 4-10 parts of polyethylene glycol and 0.5 parts of C1A type compatibilizer.

2. The toughened antibacterial PLA-based masterbatch according to claim 1, characterized in that: The particle size of the polylactic acid resin is ≤3mm, and the melt index is 2-12g / 10min; the diameter of the nano zinc oxide is ≤50nm; and the diameter of the polyhexamethylene guanidine hydrochloride is ≤100μm.

3. A method for preparing the toughened antibacterial PLA-based masterbatch according to claim 1 or 2, characterized in that: The raw materials are melt-blended according to their mass fractions, extruded and granulated to obtain the toughened antibacterial PLA-based masterbatch; the melt-blending temperature is 145° C.-180° C.

4. A toughened antibacterial PLA-based meltblown nonwoven material, characterized in that: The raw material is the toughened antibacterial PLA-based masterbatch as described in claim 1 or 2.

5. A method for preparing the toughened antibacterial PLA-based melt-blown nonwoven material according to claim 4, characterized in that: The toughened antibacterial PLA-based masterbatch according to claim 1 or 2 is melted and spun, and then subjected to hot pressing treatment and corona electret treatment in sequence.

6. The toughened antibacterial PLA-based meltblown nonwoven material according to claim 5, characterized in that: The melting temperature is 135-180° C. and the pressure is 3-5 MPa; the hot pressing temperature is 135° C., the pressure is 0.1 MPa, and the time is 7 s; the parameters of the corona electret treatment are set as follows: the electret voltage is 30 kV, the electret time is 2 min, and the electret distance is 35 cm.

7. Use of the toughened antibacterial PLA-based masterbatch according to claim 1 or the toughened antibacterial PLA-based melt-blown nonwoven material according to claim 4 in the fields of medical care, filtration separation or personal protection.

Citation Information

Patent Citations

  • Polylactic acid modified material with low temperature toughness and preparation method and application thereof

    CN110066502A

  • Preparation method and application of slow-release antibacterial polylactic acid dressing

    CN115463244A

  • Graphene modified degradable melt-blown non-woven material and preparation method thereof

    CN117684329A

  • Preparation method of long-acting antibacterial polypropylene melt-blown cloth based on nano complex reaction

    CN118621488A

  • Fully degradable non-woven fabric produced by melt-blow extrusion and application therof in production of medical masks

    GB202115180D0

Cited By

  • Antibacterial polylactic acid melt-blown non-woven material and preparation method thereof

    CN120366966A